Deriving a rate equation for the removal of manganese from solution using a gas mixture of sulphur dioxide and oxygen - Schulze-Messing, Jacobus (Department of Chemical Engineering, 2014)
The use of a sulfur dioxide - oxygen gas mixture to selectively remove manganese from other metals, such as cobalt and nickel, from leach solutions is kinetically favourable and inexpensive. However, this technology for precipitating manganese has not been used commercially, mainly due to a lack of understanding of the reaction mechanism by which the sulfur dioxide - oxygen gas mixture oxidises the manganese and the need to control the concentration of aqueous sulfur dioxide in the solution to ensure oxidising conditions. From the literature, the gas mixture is postulated to form a free radical in solution which in turn oxidises the manganese(lI) into the manganese(lIl) species, which can precipitate as manganese oxides (Mn02, Mn203, etc.). Due to the complicated and unknown reaction pathways for the oxidation of the manganese by the sulfur dioxide oxygen gas mixture, a need arose to describe the rate at which the manganese is precipitated from solution, not in terms of the exact species responsible for the oxidation, but rather as a function of the easily measurable operating parameters. From the literature, the operating parameters identified as playing a role in the rate of manganese precipitation are: the gas composition; the dissolved sulfur dioxide concentration; the dissolved oxygen concentration; the solution temperature, and the solution pH. To derive the relationship between the rate of manganese precipitation and each of the operating parameters, batch tests were conducted where one of the operating parameters was varied at a time. The dissolved sulfur species arising from the dissolution of the sulfur dioxide gas were not kept constant during the batch tests due to the high solubility of sulfur dioxide in water (the concentration of the dissolved sulfur species increased throughout all of the batch experiments). However, each of the operating parameters could be assessed as long as the concentration of the sulfur species in solution increased at the same rate for every test.